2017
DOI: 10.1055/s-0043-118347
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Significantly Improves Neurocognition, Sleep, and Blood Pressure in Primary Hyperparathyroidism: A 3-Year Prospective Follow-Up Study

Abstract: Surgery for primary hyperparathyroidism (PHPT) improves health-related quality of life (HRQoL), but it is unclear whether the effects are sustained after medium-term (>2 years) follow-up, and whether the results on some or all dimensions of HRQoL will reach that of the general population. We performed a follow-up of HRQoL on average 3.3 years after surgery for PHPT using the 15D in our patient cohort (n=124) and compared the results to those of an age- and gender-standardized general population (n=1099). We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…We chose to analyse the 12‐month data for this report because the maximum change from respective baselines occurred in both groups at this time point. Improvements in neurocognitive function after parathyroidectomy have been reported as early as 1 week in a small uncontrolled cohort study, and sustained improvements >2 years after parathyroidectomy have also been reported . The ability of a recent meta‐analysis to estimate the potential benefits of surgery versus active surveillance in mild hyperparathyroidism, including mental health benefits, was limited due to the paucity of good quality studies .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to analyse the 12‐month data for this report because the maximum change from respective baselines occurred in both groups at this time point. Improvements in neurocognitive function after parathyroidectomy have been reported as early as 1 week in a small uncontrolled cohort study, and sustained improvements >2 years after parathyroidectomy have also been reported . The ability of a recent meta‐analysis to estimate the potential benefits of surgery versus active surveillance in mild hyperparathyroidism, including mental health benefits, was limited due to the paucity of good quality studies .…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in neurocognitive function after parathyroidectomy have been reported as early as 1 week in a small uncontrolled cohort study, 25 and sustained improvements >2 years after parathyroidectomy have also been reported. 8 The ability of a recent meta-analysis to estimate the potential benefits of surgery versus active surveillance in mild hyperparathyroidism, including mental health benefits, was limited due to the paucity of good quality studies. 26 With this limitation, the authors concluded that no significant differences in neuropsychiatric symptoms were observed between surgery and active surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous observational studies have evaluated the effect of PTX in PHPT using the SF‐36 survey as well as other non‐disease‐specific questionnaires, suggesting improvement in HRQoL . An observational study by Rolighed et al HRQoL, assessed by SF‐36, were reduced in all 8 domains compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with mild or asymptomatic PHPT have decreased QoL based on generic QoL questionnaires (2, 127, 128, 129, 130). Numerous observational studies including the most recent have indicated a positive treatment effect of surgery on QoL (131, 132, 133). Randomized controlled studies have shown ambiguous results (128, 129, 130), demonstrating no significant effect of surgical treatment on QoL in patients not fulfilling the surgical criteria for PHPT, as summarized in a recent meta-analysis (134).…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%